The Nadir Oxygen-Specific Heart Rate Response in Sleep Apnea Links With the Occurrence of Acute Myocardial Infarction - Huang, Zhihua; Wu, Yanpeng; Huang, Kaizhuang; Chen, Pingyan; Chen, Jiyan; Wang, Ling (Frontiers in Cardiovascular Medicine, 2022)
Background: Little is known regarding the quantification of sleep apnea- and hypoxemia-elicited heart rate (HR) response and its prognostic significance of the cardiovascular risk. We sought to explore the impact of HR response and variability specific to obstructive sleep apnea (OSA) on the occurrence of a common cardiovascular event – acute myocardial infarction (AMI). Methods: Consecutive patients with suspected OSA were enrolled and underwent nocturnal respiratory study and electrocardiography monitoring. The minimal oxygen saturation (minSaO2) was determined from the oxygen saturation curve under a subject-specific search window. Primary HR metrics such as maximal HR in response to minSaO2 and respiratory event-specific HR variability were computed from the synchronized recordings. Multivariate regression analyses were conducted to analyze the associations of individualized HR metrics and the occurrence of AMI. Results: Of 2,748 patients recruited, 39% (n=1071) had moderate-to-severe OSA (respiratory event index, REI≥15), and 11.4% (n=313) patients had AMI. Patients with AMI experienced severer OSA, severer minSaO2 and greater HR reactions. Patients with minSaO2 <90% had an adjusted odds ratio (OR) of 1.48 (95% confidence interval [CI] 1.09–2.00, p=0.012) for AMI. Notably, minSaO2-induced elevated mean HR response (HRmean>73 bpm) was significantly associated with AMI (OR 1.72, 95% CI 1.32-2.23, p<0.001). Patients with both severe minSaO2 (<90%) and elevated HRmean carried an additive OR of 2.65 (95% CI 1.74-4.05, p<0.001) for the risk of AMI after adjustment for potential confounders. Large total power spectrum specific to respiratory events were correlated with an adjusted OR of 0.61 for AMI risk. Conclusions: Patients with substantial HR reactions to OSA-induced oxygen nadir and restricted cardiac cycle shifting to respiratory events were likely at increased risk of developing AMI. Detection of nocturnal heart rate response to hypoxemia may help improve cardiovascular risk stratification.